Software Simulation and Experiment for Production of a Pillow Block Using Sand Casting Process - Raharjo, Rudianto; Widodo, Teguh Dwi; Bintarto, Redi; Azhar, Andika; Wibisono, Aryasatya Rafli; D, Dhimas Kaukabi (International Journal of Mechanical Engineering Technologies and Applications, 2022)
Of many manufacturing processes, sand casting is one of the most widely used since there is no size limit of the workpiece. Big size product can be carried out at an affordable cost. In its process, sand casting comprises interconnected and complex series. If some of the processes are not properly carried out e.g. during solidification, will result in defects in the casting products. Simulation is an important method currently since it can model the entire metal casting process and show the dynamic character of the casting scheme. In this study, CAD is used for a 3D design on casting simulation. In this study, the grain size of molded sand, material quality and other process parameters were considered identical to all design schemes. This study aims to investigate the effect of varied design and dimensions of the gating system. It was found in this study that porosity and improper solidification were related to the improper gating and riser design.